The effect of fatigue on functional stability in the basketball players with functional ankle instability - Dehnavi, H.; Khorramnezhad, H.; Hassanpanah, H.; Hajibigloo, M. (American Journal of Sports Science, 2013)
The purpose of the present study was to assess the effect of basketball-specific fatigue on the dynamic postural control of the basketball players with functional ankle instability. The subjects in this study included 28 basketball players in the Youth League in Kerman. Their ages ranged between 16 and 21 years old. Based on the results of ankle instability questionnaire (CAIT) and the medical approval, the participants were selectively divided in two groups: a group of 16 subjects with functional ankle instability and a group of 12 healthy subjects. "Basketball Movement Specific Circuit" protocol was used to induce basketball-specific fatigue, and Y test was employed to quantify postural control. Specifically, Y test was administered as a pretest and posttest at the beginning and the end of the fatigue protocol. To make sure that the intended fatigue was really induced, Borg Scale was employed and the participants were asked to express their true feeling about the intensity of the exercise at the beginning and the end of the protocol. The result of analyzing data through dependent T-test indicated that dynamic postural control significantly decreased after the induction of fatigue in both groups. In addition, running independent T-test determined that fatigue equally affected the participants of both groups. This means that the participants in the experimental group coordinated postural control mechanisms with fatigue. Based on the results of this study, it can be concluded that both healthy players and those with functional ankle instability are susceptible to ankle sprain when they feel fatigue due to defect in postural control.